The Effect of Active and Passive Recovery Exercise in Reduring Doms (Delayed Onset Muscle Soreness): Critical Review - W. Wijianto; Ega Fahla Agustianti (P3M Universitas 'Aisyiyah Surakarta, 2022)
Background: Sport is an activity that has a positive effect on an individual. DOMS occurs when a person starts exercising after a long period of inactivity and results from an increase in the load and intensity of the exercise. DOMS is characterized by the onset of muscle soreness after exercise. Any type of activity that places an unusual load on the muscles can cause DOMS.Objective: to determine the existence of active recovery and passive recovery in reducing DOMS (delayed onset muscle soreness).Method: The study design in this research is a critical review. The data were obtained using several literature searches, namely Physiotherapy Evidence Database (PEDro), Science Direct, Google scholar, pubmed, NCBI, Jane BiosemanticResults: based on 7 articles found, 3 articles said massage with the rolling massage technique had a significant effect on reducing doms symptoms, 2 articles said it was not effective, 1 article said aerobic exercise had an effect on preventing doms and 1 article said stretching was not effective